Analysis of determinants of elderly welfare in Karangasem District, Karangasem Regency, Bali - Oktiartini, Pande Kadek Denik; Marhaeni, A.A.I.N. (Privietlab, 2024)
Increasing population mobility has resulted in many elderly individuals being left alone. This study aims to: 1) analyze the simultaneous and partial effects of income, health access, environmental conditions, and the perception of menama braya activities on the well-being of the elderly; 2) analyze the role of the perception of menama braya activities in moderating the influence of environmental conditions on the well-being of the elderly. This study uses a quantitative approach with an associative explanatory level. The population in this study consists of residents aged 60 and above in the Karangasem District, totaling 100 individuals. The sampling technique was conducted using accidental sampling combined with snowball sampling, with data collection methods including observation, structured interviews, and in-depth interviews. Data analysis was performed using moderated regression analysis. The results of the study show that: 1) income, health access, environmental conditions, and the perception of menama braya activities simultaneously have a significant effect on the well-being of the elderly; 2) income, health access, environmental conditions, and the perception of equalizing activities partially have a significant positive effect on the well-being of the elderly; 3) the perception of equalizing activities moderates (weakens) the influence of environmental conditions on the well-being of the elderly.